HISTORY AND CURRENT ACTIVITIES OF CATHOLIC COMMUNITIES IN FERGANA REGION (Scientific journal of the Fergana State University, 2023)
This article provides information on the activities of various religious denominations in Uzbekistan, in particular on the spread of Catholicism in Uzbekistan. The article also mentions the history and modern activities of the Catholic community in Fergana, as well as the fact that before and after the spread of Islam, Fergana was a region where representatives of various religions and nationalities lived in peace and harmony.